Complex Cyclic Cystems

Algebra Level 5

Let a , b , c a,b,c be non-zero complex numbers such that 2 b + 3 c a = 2 c + 3 a b = 2 a + 3 b c . \frac{2b+3c}{a}=\frac{2c+3a}{b}=\frac{2a+3b}{c}. Find the sum of all (distinct) possible values of 5 b 2 + 5 c 2 a 2 \left|\frac{5b^2+5c^2}{a^2}\right| .


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Calvin Lin Staff
May 13, 2014

Let k k be the complex number such that 2 b + 3 c a = 2 c + 3 a b = 2 a + 3 b c = k , \frac{2b+3c}{a}=\frac{2c+3a}{b}=\frac{2a+3b}{c}=k, then 2 b + 3 c = a k 2 c + 3 a = b k 2 a + 3 b = c k , \begin{aligned} 2b+3c&=ak \\ 2c+3a&=bk \\ 2a+3b&=ck, \end{aligned} adding the equations we get 5 ( a + b + c ) = k ( a + b + c ) 5(a+b+c)=k(a+b+c) .

1) If a + b + c 0 a+b+c\neq 0 then k = 5 k=5 , and solving the linear equations we easily obtain a = b = c a=b=c . Thus one value of 5 a 2 + 5 b 2 c 2 \left|\frac{5a^2+5b^2}{c^2}\right| is 10.

2) If a + b + c = 0 a+b+c=0 , since a 0 a\neq0 and b 0 b\neq 0 there exists a non-zero λ C \lambda \in \mathbb{C} such that b = λ a b=\lambda a , then c = ( 1 λ ) a c=(-1-\lambda) a . Replacing in 2 b + 3 c a = 2 c + 3 a b \frac{2b+3c}{a}=\frac{2c+3a}{b} we get 2 λ a + 3 ( 1 λ ) a a = 2 ( 1 λ ) a + 3 a λ a 3 λ 1 = 1 2 λ λ 3 λ λ 2 = 1 2 λ 0 = λ 2 + λ + 1 \begin{aligned} \frac{2\lambda a+3(-1-\lambda)a}{a}&=\frac{2(-1-\lambda)a+3a}{\lambda a} \\ \frac{-3-\lambda}{1}&=\frac{1-2\lambda}{\lambda} \\ -3\lambda-\lambda^2&=1-2\lambda \\ 0&=\lambda^2+\lambda+1 \end{aligned} Then λ = ω \lambda=\omega or λ = ω 2 \lambda=\omega^2 , where ω \omega is the primitive third root of unity. Hence, in this case, we have the solutions ( a , ω a , ω 2 a ) (a, \omega a, \omega^2a ) and ( a , ω 2 a , ω a ) (a, \omega^2 a, \omega a ) .

Finally, if ( a , b , c ) = ( a , ω a , ω 2 a ) (a,b,c)=(a, \omega a, \omega^2a ) then 5 b 2 + 5 c 2 a 2 = 5 ω 2 a 2 + 5 ω 4 a 2 a 2 = 5 ω 2 a 2 + 5 ω a 2 a 2 = 5 ω 2 + 5 ω = 5 = 5. \left|\frac{5b^2+5c^2}{a^2}\right|=\left|\frac{5\omega^2a^2+5\omega^4a^2}{a^2}\right|=\left|\frac{5\omega^2a^2+5\omega a^2}{a^2}\right|=|5\omega^2+5\omega|=|-5|=5. Analogously, if ( a , b , c ) = ( a , ω 2 a , ω a ) (a,b,c)=(a, \omega^2 a, \omega a ) we get 5 b 2 + 5 c 2 a 2 = 5 \left|\frac{5b^2+5c^2}{a^2}\right|=5 .

Therefore, the sum of all possible values of 5 b 2 + 5 c 2 a 2 \left|\frac{5b^2+5c^2}{a^2}\right| is 10 + 5 = 15 10+5=15 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...